Development and validation of manganese metabolism-related genes prognostic model in colorectal cancer and its immunological characteristics - Wu, Pei; Zhang, Yuwei (Journal of Gastrointestinal Oncology; Vol 17, No 2 (April 30, 2026): Journal of Gastrointestinal Oncology, 2026)
Colorectal cancer (CRC) is one of the most common malignant tumors, characterized by high invasiveness and mortality. Manganese serves as a pivotal trace mineral that governs the delicate balance between oncogenic development and host immune surveillance. However, the underlying mechanisms of manganese metabolism in CRC progression remain incompletely understood.